Groundwater monitoring for 1, 3‐dichloropropene in high fumigant use areas of North America and Europe. Issue 8 (1st April 2019) - van Wesenbeeck, Ian J; Knowles, Steve
Abstract: BACKGROUND: 1, 3‐Dichloropropene (1, 3‐D) is a soil fumigant used for the control of nematodes in high‐value fruit, nut and vegetable crops globally. Extensive water monitoring efforts have been undertaken over the past four decades by public and private institutions, given the widespread agricultural use of 1, 3‐D, and environmental fate and metabolism data suggesting the potential for 1, 3‐D to leach into groundwater. The aim of this study is to review the results of groundwater monitoring studies for 1, 3‐D conducted in North America and the European Union (EU) since 1980. RESULTS: Analysis of > 50 000 water samples by state and federal agencies in the USA resulted in 151 detections of 1, 3‐D. An additional 4000 samples analyzed in groundwater studies specifically targeting high 1, 3‐D use areas in Europe and the USA resulted in 74 detections of 1, 3‐D or its primary metabolites. The combined detection rate of 1, 3‐D and its primary metabolites in high‐use areas of the EU and North America was 0.7%. CONCLUSIONS: The availability of extensive groundwater monitoring information developed through decades of study supports the conclusion that soil fumigation with 1, 3‐D poses an inconsequential risk for drinking water exposure. The lack of significant detections of 1, 3‐D from targeted monitoring studies is due to the high volatility of 1, 3‐D, the rapid degradation of 1, 3‐D in most agricultural soils, the rapid degradation of 1, 3‐D and its metabolites in aerobic aquatic systems, and the rapid hydrolysis of 1, 3‐D in water. © 2019 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : Over 50 000 groundwater samples analyzed for 1, 3‐dichloropropene in high fumigant use areas in North America and the European Union show a very low detection rate of sporadic low‐level detections.